Designs of social research - "Das, D.K Lal" (Jaipur, 2008)
A research design includes the details about the problem, objectives, research questions, universe of study, sampling plan, and methodology and techniques of data collection and analysis. In other words, a design of social research aims at helping the researcher to prepare a scientific model-logical and systematic-so that it can help to execute the research project. It is against this background, this book deals with the subject in a very specific way, i.e., while in general it provides the basic of social research, its focus remains on the intricacies of various designs of social research. Besides, each chapter includes illustrations from practice, which discuss how research designs can be developed. In this way, the book meets the long felt need of a comprehensive and up-to-date text on the research designs-one of the most crucial stages in social research. Students, research scholars as well as educators will find this book useful and interesting.
Keywords: Social Research